Celery Potention as a Anti-Cholesterol - Dwi Sarwindah (Jurnal Penelitian Perawat Profesional, 2020)
Hyperlipidemia is an increase in one or all of the lipids in the bloodstream (plasma). Hyperlipidemia is divided into 3 groups, hypercholesterolemia (high cholesterol levels in the blood), hypertriglycerides (high triglyceride levels in the blood) or a mixture of both. Hypercholesterolemia can contribute to the development of coronary heart disease. One plant that is believed to have anti-hypercholesterolemic effects is celery. The purpose of the article is to determine the potential of celery as an anti-cholesterol. Article was compiled by searching literature sources through Google Scholar and NCBI from 2010-2019 with a total of 19 articles. The keywords used in the search were celery, Apium graveolens, hyperlipidemia, hypercholesterolemia, dyslipidemia, lipids, and anti-cholesterol. The method used for analysis is systematic literature review which identifies, assesses, and then interprets all findings on a research to answer a research question by summarizing research results. The results of the search for articles found that celery has the potential to be anti-cholesterol. This is because celery contains many useful compounds that can reduce total cholesterol, LDL, TGA or increase HDL levels in hypercholesterolemic conditions. The compounds are flavonoids, phthlides, unsaturated fatty acids, tannins, antioxidants and phytosterols.